DESENVOLVIMENTO DE NANOPARTÍCULAS CONTENDO CURCUMINA E CAPSAICINA E AVALIAÇÃO DE SUAS POTENCIAIS ATIVIDADES BIOLÓGICAS IN VITRO E IN VIVO - Nishihira, Vivian Shinobu Kishimoto (2019)
In recent decades, dietary manipulation has been one of the strategies to solve health problems, since nutraceuticals, natural products, extracts and bioactives have been used with a therapeutic approach. Among the bioactives are curcumin, with a high antioxidant and anti-inflammatory power, and capsaicin, which favors its uptake after oral ingestion. However, both have low aqueous solubility, a feature that makes it difficult to use them in clinical trials, and oral bioavailability, indicating a small use. To circumvent these problems, incorporating them into solid lipid nanoparticle (SLN) may allow for more efficient delivery. The development and application of new nanotechnological products are increasing in the pharmaceutical and medical areas, especially pharmaceutical nanocarriers. Given this context, this thesis is original and innovative because, for the first time, an SLN containing curcumin and capsaicin (NCC) was produced for therapeutic purposes. The method of production known as high shear rate proved to be efficient, since particles with an average size of 112 ± 4 nm, PDI of 0.242 ± 0.00 with zeta potential of -5.62 ± 0.89 mV and pH of 5.83 ± 0.32, which were analyzed by dynamic light scattering. Simulation tests confirmed the affinity between these bioactives for albumin for hydrophobic bonds. Thus, surfactants have a lower affinity for albumin than free curcumin and capsaicin. Already the test of formation of the corona protein, in contact with the culture medium, showed that the NCC shape after 24 hours in the three concentrations (5, 12 and 24 μg/mL for curcumin and 0.17, 0.4 and 0,8 μg/mL for capsaicin) that were evaluated. Cytotoxicity in biological systems showed that the NCC, at 5 μg/mL, did not alter the cell viability in the vero and RAW264.7 cultures after 24 and 48 hours. In hemolytic activity, the concentration of 50 μg/mL did not cause haemolysis at any of the times (10 - 80 min) evaluated. The antioxidant activity of the NCC was equated to its free form (CC) by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method, indicating that during NCC development it was preserved. NCC did not show genotoxicity in plasmid DNA in vitro and showed no difference in the weight of collected tissues such as liver, kidney and spleen in the in vivo toxicity assay. Based on the results obtained, it is concluded that the NCC seem safe to use and evaluated for future therapeutic purposes.